Clinical outcomes of COMOC-MG modified B-lynch stitch technique for preventing postpartum haemorrhage in a tertiary care teaching hospital - Chaudhary, Haresh A.; R. Shah, Bipinchandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum haemorrhage (PPH) remains a leading cause of maternal morbidity and mortality worldwide. Effective management often involves uterotonic drugs, but surgical interventions like the B-Lynch suture are crucial when medical treatments fail. The COMOC-MG modified B-Lynch stitch technique offers promising improvements in controlling atonic PPH. This study aimed to evaluate the clinical outcomes of the COMOC-MG modified B-Lynch stitch technique in managing PPH among high-risk obstetric patients undergoing caesarean sections at a tertiary care teaching hospital. Methods: A prospective study was conducted from January 2021 to June 2022 at C.U. Shah Medical College and Hospital, Surendra Nagar. Fifty antenatal women undergoing emergency or elective lower segment caesarean section (LSCS) with identified high-risk factors for PPH were included. Results: Participants were predominantly aged 26-30 years (52%), with 40% primigravidae and 60% multigravida. The majority of patients (94%) experienced no maternal complications, and only 6% required ICU admission. Fetal distress (36%) was the leading indication for LSCS. Anaemia was the most prevalent high-risk factor (22%). However, 88% did not require postoperative blood transfusions. Haemoglobin levels decreased significantly from a mean of 9.90 g/dl preoperatively to 8.70 g/dl postoperatively (p<0.05). The prophylactic COMOC-MG modified B-Lynch suture alone was successful in 82% of cases, with only 2% requiring hysterectomy. Conclusion: The COMOC-MG modified B-Lynch stitch technique is effective in preventing PPH in high-risk caesarean section patients, demonstrating low complication rates and favourable maternal outcomes. These findings support the technique’s use in managing atonic PPH and highlight the importance of comprehensive obstetric care.